2017
DOI: 10.1515/picbe-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Middle management’s role in strategy implementation projects: a behavioral analysis

Abstract: Abstract. The ability of businesses to adapt their strategy quickly and effectively to the changing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, it was revealed that the firms’ WP, DS and synergies, all contribute to efficient resource allocation if the individual level employees do not arouse IA within the organization. Because middle managers’ play a critical role in strategic success (Kiehne et al , 2017). Overall, the multilevel approach offers new insight into how individual-level information withhold in the context of IA affects the managements’ decision regarding internal resource allocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was revealed that the firms’ WP, DS and synergies, all contribute to efficient resource allocation if the individual level employees do not arouse IA within the organization. Because middle managers’ play a critical role in strategic success (Kiehne et al , 2017). Overall, the multilevel approach offers new insight into how individual-level information withhold in the context of IA affects the managements’ decision regarding internal resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was revealed that the firms' WP, DS and synergies, all contribute to efficient resource allocation if the individual level employees do not arouse IA within the organization. Because middle managers' play a critical role in strategic success (Kiehne et al, 2017). Overall, the multilevel approach offers…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an information security awareness program is of high importance (Vroom & Von Solms, 2002). Some studies revealed that managers must have an effective role in ISMS for a successful implementation (Kiehne et al, 2017;Soomro et al, 2015). Knowledge sharing among the employees is a key factor that can reduce the number of security incidents as the current and former employees are one root cause of information security breaches (Da Veiga & Martins, 2015b).…”
Section: Current State Of Methodologies For the Implementation Of Infmentioning
confidence: 99%